Influence of temperature on power factor and operating area of SynRM machine in automotive equipment - Mohd Azri Hizami, Rasid; Lanfranchi, Vincent; Ospina-Vargas, Alejandro; El Kadri Benkara, Khadija (Institute of Advanced Engineering and Science, 2024)
Across various applications, electrical machines are intensely replacing conventional hydraulic and pneumatic actuators in applications with a higher degree of complexity. In our previous study, a SynRM machine with a segmented rotor was designed to operate as a clutch actuator, to be placed in the gear housing which suffers from a high ambient temperature. This makes it necessary to predict the considerable potential influence of temperatures. This study evaluates the influence of winding resistance variation due to temperature on the machine power factor and its operating area. The evaluation is done for the condition of the automotive battery supply of 14 V, 50 A. An experimentally validated analytical model based on the SynRM machine phasor diagram was used to assess the torque-speed area and power factor variation. The main contribution is presented in the form of a tool represented as an abacus that allows the user of the machine to track the power factor and maximum speed for a range of winding resistance values. On a selected operating point of (Γ, N) = (0.57 N.m, 3500 rpm), it is demonstrated that the winding resistance should be reduced below 0.2 Ω, to be able to achieve the targeted speed, while the power factor is at 0.9.